Program Kemitraan Masyarakat Stimulus (PKMS) Untuk Meningkatkan Produktifitas Tempe Tradisional di Desa Wringinpitu Banyuwangi Dengan Memanfaatkan Teknologi Tepat Guna - Sartika, Dewi; Lestari, Riska Fita; Putra, Adi Pratama (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Tempe production which continues to grow along with the needs of the community and it will keep growing  because tempeh is an affordable food and it with ingredients that are very beneficial for the body. Partners of this program,  Stimulus Community Partnership Program (PKMS) are Tempe Production UMKM. PKMS activities are carried out by holding production equipment, the most important of which is the soybean crushing machine with its energy-saving skin. Based on the results of the implementation of the tools that have been carried out by partners, there is an increase in efficiency of production time compare to before and after the use of the tool. Before using the device, the time needed to produce tempe,  5 kg of soybean is 6 minutes 45 seconds. After the use of the device, the time needed in the production of tempeh 5 kg of material becomes 3 minutes 15 seconds. There is an efficiency of production time 3 minutes 30 seconds. In addition to time efficiency, the electrical load used at the time of production before and after using the device is difference. Before using the equipment, the electricity needed is costed 50 thousand for 23 days. After the use of the device, 50 thousand electric credit can be last up to 20 days. From the results of the evaluation conducted after a series of processes , the results obtained in line with expectations with a difference in net income in a month is Rp. 1,200,000, with increased income that can improve the standard of living of partners. Overall, the results of the use of soybean seed crushing machine with the husk make the production of tempe to partners more efficient in production time and the electricity costs are not high and get quite high profits. While the results of the device are better and not crushed the seeds.